Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Richard Jule Hollis, December 17, 1988 - Hollis, Richard Juleet al (1988)
Iowa Christmas bird counts of species found in Iowa City contributed by Richard Jule Hollis, December 17, 1988. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1988-1989. Epson - sheet feed